CORRELATION BETWEEN TRANSCUTANEOUS AND ARTERIAL CO2 PARTIAL PRESSURES IN ACUTE CARE. Issue 12 (23rd November 2015) - Ward, E; Hussain, S; Coats, T
Abstract : Objectives & Background: Partial pressures of carbon dioxide (pCO2 ) and oxygen (pO2 ) in arterial blood are used in emergency department (ED) settings to assess disease severity and guide management. Measurement is usually performed via arterial blood gas (ABG) analysis which is painful and invasive. Transcutaneous monitoring (TCM) of blood gases has been used extensively in neonates as an alternate means of measuring pCO2 and pO2 though its use in adults is not well researched. A good correlation is seen between TCM and ABG analysis of pCO2 in ideal conditions in highly selected patients. This study evaluated the relationship between TCM and ABG analysis in a "real world" emergency care situation. Methods: Breathless patients presenting to the ED at the Leicester Royal Infirmary requiring ABG analysis were considered for inclusion to the study. In suitable patients the TCM4 monitor (Radiometer) was attached as per manufacturer's instructions to measure tcpCO2 and tcpO2 at the time of ABG analysis. Patient demographics and clinical observations were noted. Data was initially analysed using Microsoft Excel, and Bland Altman analysis was performed using GraphPad Prism. Results: Paired measurements were recorded from 21 patients. The relationship between tcpCO2 and PaCO2 (see Figure) showed a strong correlation (R 2 =0.9), with a weaker correlation for O2 (R 2 =0.5). Bland Altman analysis showed a mean difference for pCO2 of −0.82kPa, with 95% limits of agreement from −2.49 to +0.84 kPa. For O2 the mean difference was 0.46 kPa (95% limits −5.72 to +6.64). Skin perfusion and BMI had no effect on the accuracy of TCM. TCM tracings must be evaluated for signal quality before a reading can be interpreted (in the same way that pulse oximetry readings are only valid if there is a 'good' trace). Electrode failure due to non-adherence of the fixation ring was common, often requiring re-application. In contrast to ABG sampling, TCM was very acceptable to patients with no reports of discomfort. Conclusion: Pragmatic 'real world' use of TCM in unselected emergency care patients does not show as close a relationship as previous studies however limits of agreement indicate that tcpCO2 is likely to be clinically useful in an ED setting. For pO2 the agreement was weaker however in clinical care pCO2 is often a larger determinant of treatment. A clinical trial is needed to compare standard care (current BTS COPD guideline) against treatment directed by TCMFigure 2 .